2016
DOI: 10.1108/jcrpp-08-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Victoria’s banning notice provisions: parliamentary, procedural and individual vulnerabilities

Abstract: Purpose Alcohol-related disorder in Australia’s night-time economy has precipitated an expanding regulatory and legislative framework. A key feature is the growth of police-imposed discretionary justice, one example of which are Victoria’s banning provisions. Banning notices are imposed on-the-spot, may be issued pre-emptively, but permit no right of independent appeal. However, there has been little analysis of the enactment, implementation or use of police-imposed banning provisions. The paper aims to discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In a number of respects, WA currently acts as an exemplar for the use of police-initiated patron banning provisions: barring notices can only be imposed following consideration of all available evidence by WA Police's centralised LEU. This mitigates a key concern that has been identified regarding the use of patron banning in other jurisdictions: that their permissible on-the-spot imposition, determined by the subjective decision of an individual officer, sometimes for pre-emptive reasons, can create procedural and operational unfairness; are generally not subject to independent review; and, potentially, lead to a disproportionate focus on identifiable individuals and/or groups (Farmer, 2016(Farmer, , 2018(Farmer, , 2019. The variable permissible length of barring notices enables WA Police to customise the period of exclusion to suit the circumstances of the incident.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of respects, WA currently acts as an exemplar for the use of police-initiated patron banning provisions: barring notices can only be imposed following consideration of all available evidence by WA Police's centralised LEU. This mitigates a key concern that has been identified regarding the use of patron banning in other jurisdictions: that their permissible on-the-spot imposition, determined by the subjective decision of an individual officer, sometimes for pre-emptive reasons, can create procedural and operational unfairness; are generally not subject to independent review; and, potentially, lead to a disproportionate focus on identifiable individuals and/or groups (Farmer, 2016(Farmer, , 2018(Farmer, , 2019. The variable permissible length of barring notices enables WA Police to customise the period of exclusion to suit the circumstances of the incident.…”
Section: Discussionmentioning
confidence: 99%
“…In Victoria, an Annual Report tabled in the Victorian Parliament should document banning notice numbers, locations and reasons, and include specific details by age and indigeneity. However, recent analysis has revealed that many of the Victorian data are incomplete and there is no evidence of their use to inform official understanding of how and why banning is used (Farmer, 2017a(Farmer, , 2016. In Queensland, a database of banning-related data is maintained, but it is not publicly available.…”
Section: Scrutiny and Oversight Of Police-imposed Banning Measuresmentioning
confidence: 99%
“… 4. Such as Victoria’s police-imposed banning notices (Farmer, 2017a, 2016, 2017b), the Prohibited Behaviour Orders which can be imposed in Western Australia for a range of behaviours not necessarily related to alcohol consumption (Crofts, 2010; Crofts and Mitchell, 2011) or zonal exclusion more generally (Palmer and Warren, 2014). …”
mentioning
confidence: 99%